The broad use of the Pm8 resistance gene in wheat resulted in hypermutation of the AvrPm8 gene in the powdery mildew pathogen - Kunz, Lukas; Sotiropoulos, Alexandros G.; Graf, Johannes; Razavi, Mohammad; Keller, Beat; Müller, Marion C. (BMC biology, 2023)
Background Worldwide wheat production is under constant threat by fast-evolving fungal pathogens. In the last decades, wheat breeding for disease resistance heavily relied on the introgression of chromosomal segments from related species as genetic sources of new resistance. The Pm8 resistance gene against the powdery mildew disease has been introgressed from rye into wheat as part of a large 1BL.1RS chromosomal translocation encompassing multiple disease resistance genes and yield components. Due to its high agronomic value, this translocation has seen continuous global use since the 1960s on large growth areas, even after Pm8 resistance was overcome by the powdery mildew pathogen. The long-term use of Pm8 at a global scale provided the unique opportunity to study the consequences of such extensive resistance gene application on pathogen evolution. Results Using genome-wide association studies in a population of wheat mildew isolates, we identified the avirulence effector AvrPm8 specifically recognized by Pm8 . Haplovariant mining in a global mildew population covering all major wheat growing areas of the world revealed 17 virulent haplotypes of the AvrPm8 gene that grouped into two functional categories. The first one comprised amino acid polymorphisms at a single position along the AvrPm8 protein, which we confirmed to be crucial for the recognition by Pm8. The second category consisted of numerous destructive mutations to the AvrPm8 open reading frame such as disruptions of the start codon, gene truncations, gene deletions, and interference with mRNA splicing. With the exception of a single, likely ancient, gain-of-virulence mutation found in mildew isolates around the world, all AvrPm8 virulence haplotypes were found in geographically restricted regions, indicating that they occurred recently as a consequence of the frequent Pm8 use. Conclusions In this study, we show that the broad and prolonged use of the Pm8 gene in wheat production worldwide resulted in a multitude of gain-of-virulence mechanisms affecting the AvrPm8 gene in the wheat powdery mildew pathogen. Based on our findings, we conclude that both standing genetic variation as well as locally occurring new mutations contributed to the global breakdown of the Pm8 resistance gene introgression.